Clinical validation of a novel thermophysical bladder model designed to improve the accuracy of hyperthermia treatment planning in the pelvic region. (31st December 2018) - Schooneveldt, Gerben; Kok, H. Petra; Bakker, Akke; Geijsen, Elisabeth D.; Rasch, Coen R. N.; Rosette, Jean J. M. C. H. de la; Hulshof, Maarten C. C. M.; Reijke, Theo M. de; Crezee, Hans
Abstract: Purpose: Hyperthermia treatment planning for deep locoregional hyperthermia treatment may assist in phase and amplitude steering to optimize the temperature distribution. This study aims to incorporate a physically correct description of bladder properties in treatment planning, notably the presence of convection and absence of perfusion within the bladder lumen, and to assess accuracy and clinical implications for non muscle invasive bladder cancer patients treated with locoregional hyperthermia. Methods: We implemented a convective thermophysical fluid model based on the Boussinesq approximation to the Navier–Stokes equations using the (finite element) OpenFOAM toolkit. A clinician delineated the bladder on CT scans obtained from 14 bladder cancer patients. We performed (1) conventional treatment planning with a perfused muscle-like solid bladder, (2) with bladder content properties without and (3) with flow dynamics. Finally, we compared temperature distributions predicted by the three models with temperature measurements obtained during treatment. Results: Much higher and more uniform bladder temperatures are predicted with physically accurate fluid modeling compared to previously employed muscle-like models. The differences reflect the homogenizing effect of convection, and the absence of perfusion. Median steady state temperatures simulated with the novel convective model (3) deviated on average −0.6 °C (−12%) from values measured during treatment, compared to −3.7 °C (−71%) and +1.5 °C (+29%) deviation for the muscle-like (1) and static (2) models, respectively. The Grashof number was 3.2 ± 1.5 × 10 5 (mean ± SD). Conclusions: Incorporating fluid modeling in hyperthermia treatment planning yields significantly improved predictions of the temperature distribution in the bladder lumen during hyperthermia treatment.